Mini reader survey in Mali - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Dramane Coulibaly, Chairman of the readers' committee in the documentation centre of the Rural Youth Action group in Ségou, in Mali, writes to tell the results of a survey conducted among 100 Spore readers : 70% are satisfied with the form and the...